2000
DOI: 10.1002/1521-3773(20001103)39:21<3849::aid-anie3849>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, Reversible Oxygen Atom Transfer between an Oxomanganese(V) Porphyrin and Bromide: A Haloperoxidase Mimic with Enzymatic Rates

Abstract: Synthetic manganese porphyrins and related systems have been used extensively in chemical modeling of biological monooxygenation reactions catalyzed by heme proteins. [1] They are also versatile catalysts for the oxygenation of alkanes, alkenes, and nitrogen-and sulfur-containing compounds using oxygen donors such as iodosylbenzene, sodium hypochlorite, alkyl, aryl, and hydrogen peroxide, amine Noxides, and molecular oxygen. [2] Only recently has the key oxomanganese(v) intermediate been well characterized. [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
114
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(124 citation statements)
references
References 17 publications
10
114
0
Order By: Relevance
“…Investigations in this area have been concentrated on the mechanism of the function of heme-containing enzymes such as cytochrome P-450 by designing metalloporphyrins as models [22][23][24]. Considerable attention has been paid to the oxidation of hydrocarbons catalyzed by Fe-, Mn-, and Ru-porphyrins [1,15,[25][26][27][28][29]. Although platinum porphyrins have been studied as oxygen sensing probes [30][31][32], photosensitizers [33][34][35], potential antitumor agents [36], and molecular conductors [37,38], there aren't any studies on platinum porphyrins as oxidation catalysts.…”
Section: Introductionsupporting
confidence: 54%
“…Investigations in this area have been concentrated on the mechanism of the function of heme-containing enzymes such as cytochrome P-450 by designing metalloporphyrins as models [22][23][24]. Considerable attention has been paid to the oxidation of hydrocarbons catalyzed by Fe-, Mn-, and Ru-porphyrins [1,15,[25][26][27][28][29]. Although platinum porphyrins have been studied as oxygen sensing probes [30][31][32], photosensitizers [33][34][35], potential antitumor agents [36], and molecular conductors [37,38], there aren't any studies on platinum porphyrins as oxidation catalysts.…”
Section: Introductionsupporting
confidence: 54%
“…Lastly, we also examined the stereochemistry of the epoxidation of cis-stilbene by 33 (202)(203)(204)(205). The high cis-epoxide/trans-epoxide ratio of 6 AE 1 obtained is consistent with a predominant oxomanganese(V) porphyrin oxidizing agent (206)(207)(208)(209).…”
Section: Hangman Porphyrin Constructs For Oxygen Activationmentioning
confidence: 99%
“…Meunier et al have described the chlorination of dimedone by the water-soluble porphyrin Mn(III)TMPS supported on a polyvinylpyridinium polymer [32]. The direct oxidation of bromide by oxygen atom transfer from oxo-Mn(V) complexes has been observed in our laboratory as well as the reverse reaction, i.e., oxidation of the Mn(III) porphyrin with HOBr/ OBr À [33,34]. Recently, Naruta et al [35] reported the formation and characterization of a dinuclear oxo-Mn(V) porphyrin complex.…”
Section: Introductionmentioning
confidence: 99%